Alleen op de Wereld - Malot, Hector, 1830-1907; Keller, Gerard, 1829-1899 (Salt Lake City, UT : Project Gutenberg, 2006)
"Alleen op de Wereld" by Hector Malot is a youth adventure novel published in 1878. The story follows Remi, a foundling who believes he lives happily with his mother until his pleegfather returns and sells him to a traveling Italian artist named Vitalis. Together with trained animals, they journey across France performing shows. As Remi searches for his true origins, he faces harsh winters, dangerous wolves, and unexpected friendships that test his resilience and shape his destiny. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Sans_Famille Wikipedia page about this book: https://nl.wikipedia.org/wiki/Alleen_op_de_wereld
Translation of: Sans Famille
Release date is 2006-08-15
Produced by Jeroen Hellingman and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Orphans -- Fiction; Adventure and adventurers -- Fiction; France -- History -- 19th century -- Fiction; Street entertainers -- Fiction